Preparation of CuO/SiO2 and photocatalytic activity by degradation of methylene blue - Batista, Ana P. L.; Pereira Carvalho, Hudson Wallace [UNESP]; Luz, Gustavo H. P.; Martins, Paulo F. Q.; Goncalves, Maraisa; Oliveira, Luiz C. A. (Springer Heidelberg, 2010)
A photocatalyst based on CuO/SiO2 was prepared, and evaluated for the degradation of methylene blue in aqueous medium. The photocatalyst was obtained by calcination method of copper salt, in the presence of silica. The characterization by XRD, FTIR, and TPR techniques confirmed the formation of CuO as active phase. SEM studies showed CuO deposited on the surface of SiO2. By ESI-MS, it was demonstrated that the degradation of methylene blue occurs through successive hydroxylations. Photodegradation assays showed that CuO/SiO2 was efficient for degradation, and that the material worked better in the presence of UV light.
Keywords: Photocatalyst; Photodegradation; Methylene blue; CuO/SiO2; ESI-MS